THE ROLE OF INTERNAL AUDITORS IN FRAUD PREVENTION AND DETECTION: EMPIRICAL FINDINGS FROM GENERAL BANKING - Rhayhan Prianbudi Lukman; Anis Chariri (Diponegoro Journal of Accounting, 2023)
The purpose of this research is to investigate the role of internal auditors in fraud prevention and fraud detection at banks general banking sector. The independent variable in this study is the role of the internal auditor (X) with fraud prevention (Y1) and fraud detection (Y2) as the dependent variable.This research uses primary data with questionnaires as research instruments which are distributed to 80 internal auditors at general banking sector. Of the total respondents, there were 78 respondents completed and returned the questionnaire and were used as samples in this study. SPSS version 25 is used to analyze the data. The results of the analysis of this study indicate that the role of internal auditors has a significant effect on fraud prevention and fraud detection at general banking sector. This is evident from the magnitude of the significance value of the two dependent variables, which means that the greater the role of internal auditors can increase fraud prevention and fraud detection efforts at general banking sectors.